Inhibition of Chromobacterium violaceum antibiotics production by catabolite repression - Loke, Wai Keong; Mohd Saud, Halimi (2009)
Chromobacterium violaceum is a pathogenic bacteria to human and produce antibiotics which include aerocyanidine, aerocavin, 3,6-dihydroxyindoxazene, Factor Y-T0678H (6-hydroxy-3-oxo-1,2-benzisoxazolin) and violacein, a purple pigment that gives Chromobacterium violaceum its colour. The production of purple pigment and antibiotics were controlled by quorum sensing and activated by N-acyl homoserine lactones (AHL) C6-HSL signal molecules in high cell density condition and reaches the quorum level. In high concentration of glucose, the production of purple pigment and antibiotics from C. violaceum was affected and was produced only at low nondetectable volume. This phenomenon showed that catabolite repression happened in C. violaceum and the operon to control the genes of production of purple pigment and other antibiotics were catabolite-sensitive where the operon was not maximally expressed.